Experimental Study of Aluminium Joint Plate Between AA5052 with AA5083: Application on Hull Vessel Material - Arifuddin, Andi Mursid Nugraha; Hidayat, Taufik; Pawara, Muhammad Uswah; Zulkifli, Muhammad (International Journal of Marine Engineering Innovation and Research, 2025)
Generally, the planning of the material arrangement of the aluminum hull plate is always carried out at an early stage to obtain a material formation that has good economic value. One of the strategies used to obtain economic value in shipbuilding is the use of various grades of plate material. The grade of aluminum material that is often used on ships is the 5xxx series. Where this series has many grades that can be used as ship hull material options. The price difference for each grade of aluminum material for ships is a very influential variable on the economic value of shipbuilding. However, before being applied to shipbuilding, it is necessary to test the feasibility of aluminum plate connections with variations in plate grade. The aim is to provide clear information regarding the technical feasibility of selecting material grades. Therefore, in this study, a simulation will be carried out to test the strength of the plate connection with variations in the grade of aluminum material using the experimental method. The plate joint test is carried out using only the Tensile test in the laboratory with reference to the ASTM rules. The grades of aluminum plate materials used are 5052 and 5083. Connection formations are between 5052-5052, 5083-5083, and 5052-5083. From the test results, the largest average yield stress value is 202.34 N/mm2 at the variation 5083-5083, the maximum average ultimate stress value is 261.70 N/mm2 at the variation 5083-5083. For the variation of the 5052-5083 plate connection, it still has a yield stress value that is greater than the basic yield stress of the material, namely 142.97 N/mm2. Where the percentage value of the achievement level of yield strength is 113.6% of the basic yield stress value of the material based on BKI rules. However, in achieving the ultimate stress value, it is still lower than the ultimate basic stress of the BKI rules standard material, which is 193.88 N/mm2. Where the percentage value of the level of ultimate strength achievement is 70.5% of the ultimate basic stress value of the BKI rules standard material.